(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
The study included obtaining organic extracts of local marine bacterial isolates of the genus Bacillus isolated from the coastal sediment samples of the Afamea region. which was collected from four stations during the month of October 2020. The chemical composition of the organic bacterial extracts was studied by gas chromatography-related mass spectrometry (GC/Ms). The chemical compounds of the bacterial extracts of each of the Bacillus isolates were determined. The results showed that the extracts contain the most important chemical groups such as carboxylic acids, esters, aldehydes, amines, hydrogen carbonate and their derivatives. One of the most important of these compounds that has anti-bacterial, anti-inflammatory, and anti-cancer effects. (Benzenamine, 3,5-dimethyl Octadecenoic acid (Z), Morpholine) which were found in high levels in bacterial extracts. It was also noted that some compounds have anti-inflammatory, antioxidant, and anti-toxin properties, and some of them are used as disinfectants, and in cosmetics and pharmaceuticals such as (Tetracosane, Nonacosane, Tetradecanoic acid, ethyl ester, Pentadecanoic acid).